2019
DOI: 10.31248/jasvm2018.089
|View full text |Cite
|
Sign up to set email alerts
|

Identification of causes and associated risk factors for lameness in working donkeys in and around Bishoftu

Abstract: The present study was conducted from November 2014 to April 2015 in and around Bishoftu town to determine causes, associated risk factors and owner's response to causes of lameness for lame donkeys presented to Donkey Health and Welfare Project Clinic. Accordingly, 325 lame donkeys were purposively selected for this study. Questionnaire survey and physical examination were employed as study design. Results of 325 donkey owners interviewed revealed that various causes of lameness. Among these interviewed 222 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Seventeen percent of studies (11/64) investigated lameness-related outcomes in working equids but were included in qualitative synthesis [ 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ] ( Spreadsheet S4 ). These studies were not eligible for data extraction, as the sampled population had other concurrent abnormalities (3/11; 27.3%), investigated populations of exclusively lame animals (2/11; 18.2%), the outcome was unclear or not strictly lameness-related (2/11; 18.2%), or did not provide quantitative data for the extraction or calculation of the outcomes of interest (4/11; 36.4%).…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen percent of studies (11/64) investigated lameness-related outcomes in working equids but were included in qualitative synthesis [ 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ] ( Spreadsheet S4 ). These studies were not eligible for data extraction, as the sampled population had other concurrent abnormalities (3/11; 27.3%), investigated populations of exclusively lame animals (2/11; 18.2%), the outcome was unclear or not strictly lameness-related (2/11; 18.2%), or did not provide quantitative data for the extraction or calculation of the outcomes of interest (4/11; 36.4%).…”
Section: Resultsmentioning
confidence: 99%
“…There is an assumption that owners report less lameness as compared to veterinarians and this assumption is based on surveys of horses, which have repeatedly demonstrated that owners report a lower prevalence of lameness and gait asymmetry than experts (52,53). However, donkey owners have suggested work overload as a potential cause for lameness in Ethiopia (54) and Pakistan (6), and mule owners also recognize this issue (29). Lameness is one of the main welfare issues reported in working equids globally (6,7,10,26,29) and this is an area for important future targeted owner education.…”
Section: Discussionmentioning
confidence: 99%
“…However, donkey owners have suggested work overload as a potential cause for lameness in Ethiopia (43) and Pakistan (40), and mule owners also recognize this issue (20). However, lameness is one of the main welfare issues reported in working equids globally (5,7,17,25,35,40,43,44) and this is an area for important future targeted owner education.…”
Section: Discussionmentioning
confidence: 99%
“…This assumption is based on surveys of horses, which have repeatedly demonstrated that owners report a lower prevalence of lameness and gait asymmetry than experts (41,42). However, donkey owners have suggested work overload as a potential cause for lameness in Ethiopia (43) and Pakistan (40), and mule owners also recognize this issue (20). However, lameness is one of the main welfare issues reported in working equids globally (5,7,17,25,35,40,43,44) and this is an area for important future targeted owner education.…”
Section: Discussionmentioning
confidence: 99%